Tetra-Amelia syndrome with congenital diaphragmatic hernia - A rare entity - Mina, Shyam Sundar; Arya, Sugandha; Siddiqui, Kaifi; Salhan, Meetu; Mina, Deepika (Indian Journal of Child Health, 2017)
Tetra-Amelia syndrome is a very rare disorder characterized by the absence of all four limbs. “Tetra” is the Greek word for “four” and “Amelia” refers to the failure of an arm or leg to develop before birth. This syndrome can also cause severe malformations of other parts of the body, including the face and head, heart, nervous system, skeleton, and genitalia. Tetra-Amelia syndrome with diaphragmatic defects (pulmonary hypoplasia) in a newborn is extremely rare entity. We report a very rare case of Tetra-Amelia associated with congenital diaphragmatic hernia.